Yawning and Penile Erection Frequencies Are Resilient to Maternal Care Manipulation in the High-Yawning Subline of Sprague–Dawley Rats - Dorantes-Nieto, Ángeles; Cortes, Carmen; Ugarte, Araceli; Trujillo Hernández, Angélica; Carrasco, Ángeles; Cepeda-Freyre, Héctor Alejandro; Eguibar, Jose R. (Frontiers in Behavioral Neuroscience, 2020)
Yawning is a stereotyped behavioral pattern characterized by wide open of the mouth associated with a deep inspiration followed by short expiration and it is present in all vertebrate species with low frequency. In rats it has been associated with penile erections spontaneously or after D2-like dopaminergic agonists administration. We selectively bred a high-yawning (HY) subline from Sprague-Dawley rats (SD) that yawned 20 times/h, that is one order of magnitude higher with respect to low-yawning (LY) or SD with less than 2 yawns/h. HY male rats had higher ambulation scores in an open-field arena with respect to LY rats, supporting that HY are less emotional reactive. Notably, HY dams had a different organization of maternal care with respect to that display by LY and SD dams. So, the aim of this study was to analyze the changes in maternal care on spontaneous yawning and penile erections, and after D2 agonist (-)-quinpirole as well as the expression of D2 receptors in the basal ganglia. Our results showed that HY male rats reared by SD or LY dams did not significantly differ in yawning and penile erections behaviors among the groups of male rats. The only exception is the number of penile erections in which LY male rats reared by HY dams had the highest frequencies of this behavior. Maternal care differed among the rats with the characteristic pattern in the three groups of rats with minor percentage changes. Importantly, in-fostered HY male rats had the highest (-)-quinpirole-induced yawning and penile erections supporting that maternal care is capable to influence the magnitude of these behavioral responses after D2-like dopaminergic activation. On the opposite, all subjects raised by LY and SD dams had significantly lower frequencies. In conclusion, the maternal care and environmental nest conditions during the lactation period had an impact in spontaneous and D2-like dopaminergic agonist on yawning and penile erections in both sublíneas and in the Sprague-Dawley male rats. The in-fostering and cross-fostering technique allow us to clearly demonstrate this effect.